(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Watercress (Nasturtium officinale sp.) from the Brassicae family contains phenethyl glucosinolates (gluconasturtiin) as the main glucosinolate (GLS). The enzymatic hydrolysis products by naturally-occuring myrosinase produced phenethyl isothicyanate (PEITC) which reported to possess anti-carcinogenic activity. Depending on several factors, its counterpart, phenethyl nitrile (PEN) can also be formed as hydrolysis product. This study investigated the effects of adding ascorbic acid and Fe2+ ions at different concentration on the hydrolysis of gluconasturtiin. Hydrolysis products were extracted using dichloromethane and analyzed semi-quantitatively by using GCMS. The results showed that PEITC increased at the low concentration of ascorbic acid (up to 0.06M). Similarly, addition of up to 0.06M Fe2+ ions increased PEITC; higher than 0.06M inhibits the formation of PEITC. Interestingly, similar trend for the production of PEN was detected. This study also investigated myrosinase activity both by exogenous and endogenous methods at different concentrations of ascorbic acid and Fe2+ ions using standard sinigrin as subsrat. Overall, the myrosinase activity was more active at the low concentrations of ascorbic acid. Also, the exogenous method is more efficient than endogenous. This study proved that the presence of reducing agents such as ascorbic acid and Fe2+ ions during the preparation of watercress as food would affect the production of the health-promoting PEITC.Â